On Unjust Forms of Marriage. Comments on the Discussion on Discrimination Against Same-Sex Couples (Diametros, 2018)
This article defends the thesis that, in light of the postulates of liberal ethics, it is not possible to put forward universal arguments in support of any form of marriage. The existing forms of marriage should be either deemed unjust or founded on specific arguments recognized within a particular political community and determining the understanding of justice in a particular society. It defends the thesis that the requirement of universality, and consequently of impartiality, is not met, since behind every form of marriage there is a certain “minimum” anthropological approach. Marriage is discussed as a privilege granted to particular groups by the political community. The comments are made with reference to the discussion between Krzysztof Saja and Tomasz Sieczkowski concerning the problem of discrimination against same-sex couples in Polish legislation.